Environmental Monitoring of Methane with Quartz-Enhanced Photoacoustic Spectroscopy Exploiting an Electronic Hygrometer to Compensate the H(2)O Influence on the Sensor Signal - Elefante, Arianna (Sensors (Basel), 2020)
A dual-gas sensor based on the combination of a quartz-enhanced photoacoustic spectroscopy (QEPAS) sensor and an electronic hygrometer was realized for the simultaneous detection of methane (CH(4)) and water vapor (H(2)O) in air. The QEPAS sensor employed an interband cascade laser operating at 3.34 μm capable of targeting a CH(4) absorption line at 2988.8 cm(−1) and a water line at 2988.6 cm(−1). Water vapor was measured with both the electronic hygrometer and the QEPAS sensor for comparison. The measurement accuracy provided by the hygrometer enabled the adjustment of methane QEPAS signal with respect to the water vapor concentration to retrieve the actual CH(4) concentration. The sensor was tested by performing prolonged measurements of CH(4) and H(2)O over 60 h to demonstrate the effectiveness of this approach for environmental monitoring applications.